Perancangan Sarung Bantal Batik Dengan Teknik Ecoprint : Ecoprint - Banowati Ellen Setyo Tantoko; Rudianto M. (Pusat Penerbitan LPPM ISI Bali, 2026)
The ecoprint technique is a form of textile craft development that utilizes natural materials as the primary elements in its creative process. This technique not only produces high aesthetic value but also supports environmental sustainability through the use of natural dyes. This design project aims to create sofa cushion covers for the lobby of Ayom Java Village Hotel Solo by combining batik and ecoprint techniques to strengthen the visual character and identity of the hotel lobby space. The background of this project is based on the condition of the hotel lobby, which was considered to lack a strong cultural character and atmosphere in accordance with the hotel's concept. The method employed in this project refers to Sp. Gustami’s theory of craft art creation, known as the “Three Stages and Six Steps of Art Creation,” which consists of the exploration, design, and realization stages. During the exploration stage, data were collected regarding the hotel’s characteristics, batik techniques, ecoprint techniques, and the selection of suitable leaves and natural dyes. The design stage focused on developing motifs and design compositions, while the realization stage involved the production of sofa cushion covers using a combination of batik and ecoprint techniques. The results indicate that the combination of batik and ecoprint techniques utilizing natural dyes can produce textile products that are aesthetically appealing, culturally valuable, and environmentally friendly. The integration of batik motifs with the natural imprints of leaves creates a unique visual character that enhances the identity of the lobby space at Ayom Java Village Hotel Solo. Furthermore, the resulting product has the potential to serve as an alternative interior decoration solution that supports sustainability in the hospitality industry through the use of natural materials and environmentally responsible production processes.